Criteria for the optimal financing model of public theatres - Małgorzata Gałecka; Katarzyna Smolny (Review of Economic Perspectives, 2019)
The research is part of a wider research problem, whose aim is to find an optimal financing model for cultural institutions in Poland. The purpose of this research is to evaluate the performance indicators of municipal and regional theatres in the context of accessibility to cultural public services. The study forms a verification of previously distinguished indicators of the effectiveness of cultural institutions with a general direction: how to find an optimal financing model of public dramatic theatres. The current research problem is the accessibility of public dramatic theatres in the absence of criteria for the allocation of statutory subsidies. We hypothesise that the absence of criteria for the allocation of statutory subsidies highly diversifies the accessibility of performing arts organisations. The object of study is public dramatic theatres in Poland in the period 2011-2015. We investigated the indicators having an impact on the level of accessibility of public theatres. The statistical methods used allowed us to identify criteria affecting availability. These criteria are recognized in the literature. In addition, we indicate the level of diversification of accessibility by individual public theatres.
Keywords: H2; H7; H18; 330; accessibility; cultural economics; effectiveness; Hellwig’ s methods; per-forming arts organisations